Serum S100A12 (EN-RAGE) levels in patients with decreased renal function and subclinical chronic inflammatory disease - Zakiyanov, Oskar; Kalousová, Marta; Kříha, Vítězslav; Zima, Tomáš; Tesař, Vladimír (Kidney & blood pressure research, 2011)
BACKGROUND: The calcium-binding protein S100A12 (EN-RAGE) causes inflammation through interaction with the multiligand receptor for advanced glycation end products (RAGE). The aim of the study was to determine S100A12 levels and describe their relationship to inflammatory markers in patients with decreased renal function. METHODS: The studied group consisted of 46 patients with various degrees of chronic renal insufficiency (CHRI), 31 long-term hemodialysis (HD) patients and 24 healthy controls. S100A12 and soluble RAGE were assessed immunochemically (ELISA), and routine biochemical parameters were measured. RESULTS: S100A12 levels were not different in CHRI (166 ± 140 ng/ml) and HD patients (127 ± 101 ng/ml) compared to controls (126 ± 106 ng/ml; p = 0.20, n.s.). In CHRI patients, S100A12 correlated with C-reactive protein (CRP) levels, orosomucoid, and inversely with α(2)-macroglobulin. In HD patients, S100A12 correlated with age, CRP, orosomucoid, fibrinogen and leukocyte levels. In multivariate regression analysis after adjustment for age, S100A12 levels remained correlated with: orosomucoid in CHRI patients; CRP, leukocytes, fibrinogen and negatively with sRAGE in HD patients; and leukocytes in controls. CONCLUSIONS: Although S100A12 levels were not elevated in patients with decreased kidney function, a relation to markers of inflammation was found. Further studies are required to demonstrate the significance of S100A12 in patients with decreased renal function.
Keywords: senioři; protein S100A12; Renal Insufficiency, Chronic; chronická renální insuficience; mediátory zánětu; S100A12 Protein; Middle Aged; mužské pohlaví; Adult; Inflammation Mediators; Kidney Function Tests; proteiny S100; ženské pohlaví; Humans; S100 Proteins; biologické markery; ledviny; lidé středního věku; vyšetření funkce ledvin; Kidney Failure, Chronic; dospělí; Kidney; Biomarkers; chronické selhání ledvin; Female; Aged; lidé; Male